The importance of data visualization: teaching art history through timelines - PUȘCAȘIU, Voica (Studia Universitatis Babeș-Bolyai Digitalia, 2017)
This research wishes to consider the venerable, but relatively marginal use of timelines as means of visualizing coexisting historical events and figures with special emphasis on Art History, a domain where it loses many of its inherent faults and manages to functional. The use of digital tools in humanities research is on the rise, yeilding interesting results as the timelines are now able to take on new forms. The benefits are thus increased and this chronological representation complements the traditional and established method, especially when it comes to teaching a subject that contains such ample amounts of data.